A virulent phage JHP against Pseudomonas aeruginosa showed infectivity against multiple genera. (23rd April 2016) - Khawaja, Komal Ameer; Rauf, Mahd; Abbas, Zaigham; Rehman, Shafiq ur
Abstract : The resistance to antibiotics in clinically important bacteria is one of the major global health concerns. Phage therapy could be one reliable alternative therapeutic strategy to combat these superbugs. In this study, we assessed host range of a novel bacteriophage, JHP, and characterized for its potential use in phage therapy. The bacteriophage demonstrated infectivity over a broad range of genera including multidrug resistant clinical isolates of Pseudomonas aeruginosa, members of family Enterobacteracae, and other important human pathogens. The antibacterial activity was highest at pH 7, and at temperature of 37 °C. The phage lytic activity gradually decreased till 60 °C and showed no activity when temperature was further raised. The bacteriophage could safely be stored at 4 °C or −20 °C. The latent period of the bacteriophage was 25 min and showed a burst size of 433 virions per cell. The size of JHP genome was approximately 30 kb. Family, Siphoviridae was assigned to JHP based on its icosahedral head with non‐contractile tail. The diameter of JHP head and tail length was found 115 and 152 nm, respectively. To sum up, the broad spectrum Siphoviridae phage JHP is an ingenious candidate for phage therapy.